Landscape ornamentation of rural homes - Jones, Marian Elizabeth (My University, 1896)
Introduction: The problem whether or not woman will ever be able to compete with man in the pursuit of science, remains yet to be solved. Her first and greatest duty is in the home, and whatever pertains to the home she considers of the utmost importance. Of the fine arts, Landscape gardening is the one in which she might show herself to be as proficient as man.
Citation: Jones, Marian Elizabeth. Landscape ornamentation of rural homes. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Women; Man; Science; Home; Landscape gardening; Theses; Manuscripts (documents)